I differenti effetti politici di una rivolta: il ’68 in Italia e in Germania - Caciagli, Mario (SocietàMutamentoPolitica, 2018)
The political scientist Claus Leggewie with his essay Der Mythos des Neuafangs (1996), dedicated to the stages of foundation and refoundation of the Bundesrepublik, motivates the author to further and meditated comparative reflection on the different effects of the student revolution of the Sixty-eight on the Italian political system and on the German one. Also from the point of view of an Italian political scientist, ‘68 represented a milestone in the process of democratization of Western German society and the consolidation of its political-party system, born fragile in 1949. The analysis shows, instead, how in Italy a series of circumstances prevented the party and political system from using to renew the resources that the movement had freed. The ensuing system crisis will lead to the collapse of the First Republic.